D-dimer Level and Diabetes in the COVID-19 Infection. (September 2021) - Miri, Chaymae; Charii, Hajar; Bouazzaoui, Mohammed-Amine; Laouan Brem, Falmata; boulouiz, Soumia; Abda, Naima; Kouismi, Hatim; Bazid, Zakaria; Ismaili, Nabila; El Ouafi, Noha
Introduction: Diabetes is the most common of comorbidity in patients with SARS-COV-2 pneumonia. Coagulation abnormalities with D-dimer levels are increased in this disease. Objectifs: We aimed to compare the levels of D-dimer in diabetic and non-diabetic patients with COVID 19. A link between D-dimer and mortality has also been established. Materials: A retrospective study was carried out at the University Hospital Center of Oujda (Morocco) from November 01st to December 01st, 2020. Our study population was divided into two groups: a diabetic group and a second group without diabetes to compare clinical and biological characteristics between the two groups. In addition, the receiver operator characteristic curve was used to assess the optimal D-dimer cut-off point for predicting mortality in diabetics. Results: 201 confirmed-COVID-19-patients were included in the final analysis. The median age was 64 (IQR 56-73), and 56% were male. Our study found that D-dimer levels were statistically higher in diabetic patients compared to non-diabetic patients. (1745 vs 845 respectively, P  = 0001). D-dimer level > 2885 ng/mL was a significant predictor of mortality in diabetic patients with a sensitivity of 71, 4% and a specificity of 70, 7%. Conclusion: Our study found that diabetics with COVID-19 are likely to develop hypercoagulation with a poor prognosis.